PEMEROLEHAN FONOLOGI DAN SINTAKSIS (SEBUAH STUDI KASUS PADA ANAK USIA 2 TAHUN) - Hasan Ayuba (Al-Lisan: Jurnal Bahasa, 2016)
This research aims to describe the phonological and syntaxtical acquistion of two years old child. The type of this research is a case study research. The research data is spoken record obtained from the subject conversation in a video form. The recording process consists of two phases. The first phase, the subject is let to speak naturaly which is intended to know phonological and syntaxtical of the subject. The second phase, the subject is stimulated to speak in order to know the difference between phonological and syntaxtical of the subject. The result of the research are: a) the phonological and syntaxtical acquisition of the subjectare revolving on the unmeaningfull words. The words occured in this phase are pronoun. b) after being simulated, the phonological and syntaxtical acquisition of the subjectare revolving on meaningfull words which encompass nouns, one word-utterance, two words-utterance, and diftongs. Penelitian ini bertujuan untuk menggambarkan pemerolehan fonologi dan sintaksis dari seorang anak berumur dua tahun. Jenis penelitian yang digunakan adalah penelitian studi kasus. Data penelitian berupa rekaman pembicaraan yang didapatkan dari percakapan subyek penelitian dalam sebuah video. Pengambilan rekaman terdiri dari dua fae. Fase yang pertama, subyek pada penelitian ini dibiarkan secara natural dan direkam Fonologi dan Sintaksis yang dia hasilkan. Fase kedua adalah dengan merangsang subyek pada penelitian ini untuk berbicara